SURVEY OF FAST FOOD CONSUMPTION PATTERNS AND HYPERTENSION RISK AMONG PRODUCTIVE-AGE INDIVIDUALS IN KAYU PUTIH VILLAGE, 2026 - Maria Magdalena Dwi Wahyuni; Tanti Rahayu; Karmelo Askeri Sogen; Iffah Atiqah Sari; Maria Yuliana Mina Wora; Marshanda Ananda Pandie; Vincentia Yunita Dania Moghu (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
Hypertension is rising among the productive-age population, with fast food consumption being a significant modifiable factor. This study aimed to provide a descriptive overview of fast food consumption patterns and the hypertension risk profile in Kayu Putih Village in 2026. This quantitative, descriptive cross-sectional study (rapid survey) involved 210 respondents selected via simple random sampling. Data were collected through face-to-face interviews using a structured questionnaire. Fast food consumption habits were categorized as “good” or “bad” based on a composite score of frequency, food type, and portion size, using the median as the cut-off point. Hypertension risk was determined based on self-reported medical history and symptomatic assessment rather than direct clinical measurement. Results showed that 44.76% of respondents consumed fast food 1–2 times per week, with instant noodles (56.19%) and fried chicken (52.86%) being the most preferred types. While 68.57% were categorized as having bad consumption habits, only 4.76% were identified as being at risk for hypertension. It is concluded that while fast food consumption is common, the perceived hypertension risk remains low. Strengthening health promotion regarding balanced nutrition is necessary for prevention.